Loss of Hyaluronan and Proteoglycan Link Protein-1 Induces Tumorigenesis in Colorectal Cancer - Wang, Yao; Xu, Xiaoyue; Marshall, Jacqueline E.; Gong, Muxue; Zhao, Yang; Dua, Kamal; Hansbro, Philip M.; Xu, Jincheng; Liu, Gang (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is the third most common diagnosed cancer worldwide, but there are no effective cures. Hyaluronan and proteoglycan link protein-1 (HAPLN1) is a component of the extracellular matrix (ECM) proteins and involved in the tumour environment in colon. Transforming growth factor (TGF)- is a key cytokine that regulates the deposition of ECM proteins in CRC. However, the role of HAPLN1 in TGF- contributions to CRC remains unknown. We found that the mRNA expression of HAPLN1 was decreased in tumours from CRC patients compared to healthy controls and normal tissue adjacent to tumour using two existing microarray datasets. This was validated at the protein level by tissue array from CRC patients (n=59). HAPLN1 protein levels were also reduced in human CRC epithelial cells after 24 hours of TGF- stimulation, and its protein expression correlated with type I collagen alpha-1 (COL1A1) in CRC. Transfection of HAPLN1 over-expression plasmids into these cells increased protein levels, but reduced COL1A1 protein, and tumour growth and cancer cell migration. TGF- stimulation increased Smad2/3, p-Smad2/3, Smad4 and E-adhesion proteins, however HAPLN1 over-expression restored these proteins to baseline levels in CRC epithelial cells after TGF- stimulation. These finding suggest that HAPLN1 regulates TGF- signalling pathway to control collagen deposition via TGF- signalling pathway and mediates E-adhesion to control tumour growth. Thus, treatments that increase HAPLN1 levels may be a novel therapeutic option for CRC.